PENINGKATAN KETERAMPILAN MEMBACA INTENSIF MELALUI STRATEGI DIRECTED READING THINKING ACTIVITY (DRTA) BERBANTUAN GAMBAR SERI SISWA KELAS III A SDN SUNGGUMINASA V: PTK - Maulidya Apriana; Ipal Mantopani (STKIP Subang, 2024)
The main problem in this research is how to apply the directed reading thinking activity strategy to be able to describe the increase in intensive reading skills in class III A students at SD Negeri Sungguminasa V. This research aims to describe increasing student activity in intensive reading learning through the Directed Reading Thinking Activity strategy assisted by a series of images and improving the intensive reading skills of class III A students at SDN Sungguminasa V through the Directed Reading Thinking Activity strategy assisted by a series of images. This type of research is class action research (Class Action Research) which consists of two cycles where each cycle is carried out in two meetings. Research procedures include planning, implementing actions, observing and reflecting. The subjects in this research were 27 students in class III A of Sungguminasa V Public Elementary School. The results of the research show that: a) cycle I student activities obtained an average score of 26.3 with very good criteria. In cycle II, the score obtained was 27.87 with very good criteria; b) students' intensive reading skills in cycle I averaged a score of 72.6 with the percentage of completeness achieved being 55.5% with 15 students having achieved completeness and 12 other students not yet. In cycle II the average obtained was 85.3 with a completion percentage of 100% with 27 students or all students having achieved completeness. Based on the results of the research above, it can be concluded that the directed reading thinking activity strategy assisted by series of images is able to increase student activity and the intensive reading skills of class III A students at SDN Sungguminasa V.